Environmental Risks of Nanotechnology: Nanoparticles and Nanostructures - Delgado, Gean Carlo (2006)
Nanotechnology, that manipulates matter to the thousand millionth of meter, is assumed as one of the technological fronts of the 21st century of greater expectations and implications.  For the moment, most of the advances are centered in the development of new nanomaterials for different use. The unique properties of the nanoparticles and nanostructures that compose them suggest potential implications on the environment and on life due to the uncertainty of their interactions and effects.  How the environmental risk of nanotechnology is being assumed, evaluated, confronted and distributed are aspects object of this reflection.